A model of idiosyncratic deal-making and attitudinal outcomes. Issue 3 (11th April 2016) - Ho, Violet T.; Tekleab, Amanuel G.
Abstract : Purpose: – The purpose of this paper is to disentangle the relationship between the request of idiosyncratic deals (i-deals) and the receipt of such deals, and investigate the moderating roles of human capital (gender and industry experience) and social capital (leader-member exchange (LMX)) in this relationship. Attitudinal outcomes of i-deals receipt are also examined. Design/methodology/approach: – Data were collected from 244 alumni of a Midwestern public university. Findings: – The positive relationship between i-deals request and receipt was stronger at higher than at lower levels of LMX. Receiving i-deals was related positively to job satisfaction and affective commitment, and negatively to turnover intention. Research limitations/implications: – The authors provide a nuanced perspective of i-deals by separating employees' request from their receipt of i-deals, and identifying contingent factors that determine whether i-deal requests are successful. Practical implications: – For employees, cultivating a strong relationship with one's supervisor can yield benefits that extend to i-deals negotiation. Providing i-deals to deserving workers can boost employees' work attitudes. Originality/value: – Previous studies have operationalized the i-deals construct as requesting and receiving the deal, thereby excluding the possibility that employees may have requested but did not receive the i-deal. This is one of the first studies to disentangle these two concepts, thereby providing a more balanced and representative view of i-deal-making in organizations.